28 hours later : the zombie movie [videorecording (DVD)] / You Don't Say Media presents. - Skoog, Eric; Skoog, Eric; Skoog, Eric; Seibert, Daniel M.; Swoboda, Frank; Archer, Kate; Bundy, Clancy; Ferger, Mychal; Lewis, Josh; Moore, Jacob; Villabrille, Paul; Culp, Rob (You Don't Say Media, 2010)
A film crew is in the midst of making a zombie movie, when suddenly everything becomes very, very real.